Exploring the role of indoor microbiome and environmental characteristics in rhinitis symptoms among university students - Fu, Xi; Shama, Aga; Norbäck, Dan; Chen, Qingsong; Xia, Yun; Zhang, Xin; Sun, Yu (Frontiers in Microbiomes, 2024)
Rhinitis is one of the most prevalent chronic respiratory diseases worldwide. There is emerging evidence suggesting that the indoor microbiome may contribute the onset and exacerbation of rhinitis symptoms, but comprehensive studies on this topic remain scarce. In this study, we assessed the microbiome assemblage of settled air dust collected in Petri dishes in 86 dormitory rooms of Shanxi University, China using 16s rRNA sequencing. A self-administered questionnaire, including questions about rhinitis symptoms and personal information, was completed by 357 students residing in these dormitories. Logistic and linear regression model was applied to examine the associations between environmental characteristics, indoor microbiome, and rhinitis.The most abundant genera in the dormitories were Ralstonia (15.6%), Pelomonas (11.3%), Anoxybacillus (9.3%) and Ochrobactrum (6.2%). Taxa richness in the class of Actinobacteria and Fusobacteriia was negatively/protectively associated with rhinitis (p<0.05). Six bacterial genera, including those from Actinobacteria (Actinomyces), Fusobacteriia (Fusobacterium), and Bacteroidetes (Prevotella and Capnocytophaga), were negatively/protectively associated with rhinitis. Conversely, seven genera, predominantly from Alphaproteobacteria and Betaproteobacteria (Sphingomonas, Caulobacter, uncharacterized Caulobacteraceae and Comamonadaceae), were positively associated with rhinitis. Living in higher floor level and higher indoor PM2.5 concentrations were associated with a higher abundance of taxa potentially protective against rhinitis and a lower abundance of taxa potentially increasing the risk of rhinitis (P<0.01). However, having curtain indoor and higher indoor CO2 concentrations were associated with a lower abundance of taxa potentially protective against rhinitis and a higher abundance of taxa potentially increasing the risk of rhinitis (P<0.01). This study enhances our understanding of the complex interactions between environmental characteristics, indoor microbiomes, and rhinitis, shedding light on potential strategies to manipulate indoor microbiota for disease prevention and control.